FUNCTION OF LEADERSHIP OF THE HEAD OF SCHOOL AND CLIMATE ORGANIZATION IN MEETING TEACHER SATISFACTION - Afero, Baghdad; Dekawati, Ipong; Pujiyati, Wresni (EARR (Educational Administration Research and Review), 2018)
This research was conducted in three State Vocational High Schools at Indramayu sub-district and Sindang sub-district. The issue became a study in this research is not optimal teacher job satisfaction including the working conditions and conditions that do not match expectations, comfort in work and relationships with superiors. Focused directed at factors that influenced teacher job satisfaction. Principles of leadership function and organizational climate are the factors that thought to have influence on the teachers job satisfaction. Therefore the study examines three variables, namely the principles of leadership function (X1), organizational climate (X2) and teachers job satisfaction (Y). This research used descriptive and verification methods. Data collection techniques used question form. The respondents were civil servants of The State Vocational High School 1 Indramayu, State Vocational High School 2 Indramayu and State Vocational High School 1 Sindang as many as 87 people. The data technique analyzed using the regression. The result of the data analysis revealed that the principles of leadership function included in very good category, organizational climate in very good category, meanwhile teachers job satisfaction at The State Vocational High School 1 Indramayu, State Vocational High School 2 Indramayu and State Vocational High School 1 Sindang included in very good category. Based on the analyzed of regression, the result revealed that the principles of leadership function and organizational climate are both partially and simultaneously, has a positive and significant influence toward teacher job satisfaction.